2023
DOI: 10.1039/d3lc00337j
|View full text |Cite
|
Sign up to set email alerts
|

Precise, wide field, and low-cost imaging and analysis of core–shell beads for digital polymerase chain reaction

Abstract: Digital droplet reactors have become a valuable tool for the analysis of single cells, organisms, or molecules by discretising reagents into picolitre or nanolitre volumes. However, deoxyribonucleic acid (DNA) based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We employed a customised image processing algorithm to take all these factors into consideration and to achieve robust evaluation. 46,47 The results also demonstrated that all DNA molecules were encapsulated into the core without contaminating the shell. Fig.…”
Section: Pcrmentioning
confidence: 81%
See 1 more Smart Citation
“…We employed a customised image processing algorithm to take all these factors into consideration and to achieve robust evaluation. 46,47 The results also demonstrated that all DNA molecules were encapsulated into the core without contaminating the shell. Fig.…”
Section: Pcrmentioning
confidence: 81%
“…Polymerization and subsequent solidification of the shell prevented the coalescence of sample droplets during the subsequent PCR process and ensured their long-term stability. 46,47 In the present study, we utilised several liquid systems to study the impact of material properties on the position of the core in the shell droplet. We first studied the surfactant concentration in the continuous phases introduced from inlets 3 and 4 as the spacer fluid, while deionized water was used as the core phase.…”
Section: Preparation Of Core-shell Particlesmentioning
confidence: 99%
“…With a liquid core encapsulated by a solid shell, liquid beads serve as reservoirs for controlled release of therapeutic agents in cell therapy, tissue regeneration, and provide three-dimensional (3D) cell culture environments for research and medical applications (Liu et al 2021 ; Sun et al 2018 ). In our previous works, we also demonstrated culturing microalgae (Tran et al 2024 ) and amplification of deoxyribonucleic acid (DNA) (Yadav et al 2023 ) in liquid beads. In addition, these beads are also useful in food processing (Wu et al 2017 ), cosmetics (Foglio Bonda et al 2020 ), and digital microfluidics (Kong et al 2013 ; Wu et al 2023 ).…”
Section: Introductionmentioning
confidence: 94%
“…Liquid beads have a solid shell, whereas liquid marbles have a soft powdered coating as shell. The shell material of liquid beads can be either organic polymers or organic-inorganic composites (Yadav et al 2023 ; Yang et al 2013 ). Liquid beads have gained increasing attention due to their distinctive core and shell structure enabling unique applications.…”
Section: Introductionmentioning
confidence: 99%